Globalité des savoirs des pêcheurs artisans dans l’appréhension des changements de l’environnement marin. - Adama Mbaye (VertigO)
This article analyses the nature and scope of the knowledge of Senegalese artisanal fishermen in their understanding of the risks due to changes in the marine environment. Based on individual and group interviews with fishermen from the guet-ndarienne community, it shows that fishermen interpret or predict the occurrence of variations or changes in environmental parameters such as sea state, swell, wind, rain, the nature of the seabed and species present using indicators based on the apparent movement of the stars, the behaviour of trees or animals (marine or terrestrial), the taste, colour or shape of certain elements of their environment. These ways of understanding the marine environment of fishermen based on their empirical knowledge can be subjected to scientific experimentation and validation and can be appropriated by the scientific community and be of universal use in order to contribute to the means of reducing the risks due to global changes.